Programa Ciência sem Fronteiras: desdobramentos e análise das possíveis contribuições à formação acadêmica dos bolsistas - Ramos, Aline Gonzaga (2016)
This work analyzes the Science Without Borders Program - SwB in a higher educational institution – HEI, seeking to comprehend aspects related to contributions to the academic education of scholarship students. This Program aims on the idea to focus on innovation and strengthening the technology and industry with the formation of highly qualified human resources in strategic areas to generate economic growth and social development. The actions seek student and professional mobility, making possible an exchange of experience in educational institutions and the world of research and international companies. Thefore, the analysis of the SwB Program becomes crucial so that the work becomes increasingly effective. The methodology used for this work was documentary research and application of questionnaire to the scholarship students to support the assumptions made about the aspects related to the academic education of scholarship students and the implementation of the Program. The results evidence that the Program is important to the academic and professional education of scholarship students, but some problems, such as lack of information, monitoring of the exchange and validation of subjects studied were detected and are liable to solution, thus seeking, excellence in institutional performance of the Brazilian HEI and the achievement of the objectives outlined by the Program